2015
DOI: 10.1590/0100-2945-023/14
|View full text |Cite
|
Sign up to set email alerts
|

Adubação N-K No Abacaxizeiro ‘Brs Imperial’ - I - Efeito No Desenvolvimento E Na Floração Da Planta

Abstract: RESUMO -o abacaxizeiro 'BRS imperial' é cultivar resistente à fusariose, com folhas sem espinhos, e que carece de informações técnicas específicas para o seu manejo. Este trabalho teve como objetivo avaliar o efeito de doses de n e K 2 O no desenvolvimento vegetativo, na floração e nos atributos de desenvolvimento da folha 'D' do 'BRS Imperial', buscando estabelecer parâmetros da planta para a indução artificial do florescimento. em delineamento em blocos ao acaso e cinco repetições, testaram-se quatro doses d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
2
5
0
2
Order By: Relevance
“…In the current study, it was observed the emission of 27 leaves from 120 to 300 DAP, and the IMP cultivar produced some 14 leaves between DAT 30 to 150. This agrees with the periodicity of leaf production given by Oliveira et al (2015) for this cultivar.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, it was observed the emission of 27 leaves from 120 to 300 DAP, and the IMP cultivar produced some 14 leaves between DAT 30 to 150. This agrees with the periodicity of leaf production given by Oliveira et al (2015) for this cultivar.…”
Section: Resultssupporting
confidence: 91%
“…In studies of pineapple cv. IMP, Oliveira et al (2015) found that more leaves were producted between 180 and cultivar FANT benefited from extended post-transplantation greenhouse time, as leaves initially measuring 15 cm, had doubled their length by 150 DAP, to reach a mean of 30.36 cm. This contrasts with results for cv.…”
Section: Resultsmentioning
confidence: 99%
“…There was correlation of the fruit mass with crown of 0.55 and 0.63 in relation to the length and fresh mass of leaf D, respectively. Similar results were found by Oliveira et al (2015b) where for cv. Imperial they reported correlation between the mass of the fruit and the mass of leaf D, being 56 g the maximum mass observed in leaf D. For this mass, the fruit mass of 1,096 g was estimated.…”
Section: /9supporting
confidence: 90%
“…Studying the Imperial cultivar in a hydroponic system, Ramos et al (2013) verified leaf length D of 66.2 cm with the complete solution, a value close to this study. Studying the same cultivar, under dry conditions, Oliveira et al (2015b) reported mean leaf D length of 75.15 cm but found no effect of N and K doses.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation